(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
The present study was undertaken to investigate the impact of colostral period on colostrum composition and immunoglobulin (Ig) concentration of cows and she-camels. The study was conducted at two sites, the U. of K. Dairy farm and Tamboul Camel Research Centre (TCRC). Six cows and two she camel, immediately post-partum were selected from the U. of K. Dairy farm, and three post calving she-camels, were chosen from the TCRC.. A total of 66 colostrum samples representing two samples from each animal for the first three colostral days were collected and subjected to chemical analysis, by colostremeter apparatus. The results revealed significant (P<0.01) differences in the composition of the two species. The bovine colostrum significantly ( P<0.05) exceeded camel colostrum in fat and ash while CP, TS, lactose and Ig were significantly (P<0.05)higher in camel colostrum. The Ig concentration in camel colostrum was twice that of cow colostrum. In both species, the first day colostrum samples significantly (P<0.05) secured the highest CP, fat, TS and Ig compared to the 2nd and 3rd day samples, while the lactose concentration was lowest in the first day samples and increased gradually in the successive days. The concentration of Ig in the first day samples was twice its concentration in the 2nd and three times greater in the 3rd day samples indicating the importance of feeding colostrum to the new born during the first 24 hours postpartum.